Bacteriological qualities of sources of domestic water supply and prevalence of typhoid fever in some communities of Enugu State, Southeast, Nigeria: a cross-sectional study - Umegbolu, Emmanuel I.; Offor, Moses E. (International Journal Of Community Medicine And Public Health, 2017)
Background: From the public health point of view, the microbiological properties of domestic water supply are the most important parameters of domestic water supply because of the propensity for microbial water-related diseases. In Enugu State, statistics have shown that reported cases of waterborne diseases (including typhoid fever) have been on the increase since 2003. The aim of the study was to determine the bacteriological qualities of domestic water supply and prevalence of typhoid fever in five communities of Enugu State in connection with the rising incidence of typhoid fever in the state. Methods: This was a cross-sectional study of sources of domestic water supply and prevalence of typhoid fever in five rural communities of Ezeagu Local Government Area. 297 copies of structured questionnaire, 10 grab water samples analysed using the membrane filtration method and 227 blood samples collected for Widal test were used to generate the data for the study, analysed as frequency distributions, t-test of means difference and Pearson product moment correlations using MaxStat (version 3.60) statistical software. Results: 2 (40%) of the 5 communities complied with the WHO standard for faecal coliform counts. Prevalence of typhoid fever was high in all the communities (71.4%-100%). Only faecal coliform counts correlated positively and strongly (r=0.69) with prevalence of typhoid fever. Conclusions: Since faecal coliform counts correlated positively and strongly (r=0.69) with prevalence of typhoid fever, improving the bacteriological qualities of domestic water supply may help to reduce the prevalence of typhoid fever.